APPLICATION OF ACCOUNTING INFORMATION IN INFLUENCING THE FINANCIAL PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES WITH FINANCIAL LITERACY AS A MODERATOR VARIABLE - Budi Gautama Siregar; Aswadi Lubis; Zaki Zaini (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
The low utilization of accounting information by MSEs actors in managing and controlling business finances has resulted in suboptimal financial performance of MSEs. The objective of this study is to analyze the effect of the application of accounting information on the financial performance of MSEs with financial literacy as a moderator variable. The proper application of accounting information is expected to enhance the financial performance of MSEs, considering the importance of accounting information in making more accurate business decisions. Data were collected through questionnaires distributed to MSEs actors, with a purposive sampling method. The analytical technique applied is moderating regression analysis to test the relationship between the research variables. The results show that the application of accounting information has a positive and significant effect on the financial performance of MSEs. In addition, financial literacy is proven to moderate this relationship by strengthening the influence of accounting information on financial performance.